Complete recovery of fulminant cytotoxic CD8 T‐cell‐mediated myocarditis after ECMELLA unloading and immunosuppression. (2nd June 2020) - Jurcova, Ivana; Rocek, Jan; Bracamonte‐Baran, William; Zelizko, Michael; Netuka, Ivan; Maluskova, Jana; Kautzner, Josef; Cihakova, Daniela; Melenovsky, Vojtech; Maly, Jiri
Abstract: A 19‐year‐old woman with no previous cardiac history was admitted to the hospital with third‐degree atrioventricular block and left ventricular dysfunction. Her condition quickly deteriorated to severe biventricular failure and cardiogenic shock requiring mechanical circulatory support. An endomyocardial biopsy revealed lymphocytic myocarditis with no PCR‐detectable viral genomes, with CD8 T‐cell predominance and pro‐inflammatory macrophage expansion shown by myocardial flow cytometry. The therapy consisted of immunosuppression (high‐dose methylprednisolone) and temporary mechanical circulatory support with enhanced ability to achieve left ventricular unloading by combination of extracorporeal membrane oxygenation with Impella (ECMELLA). After 2 weeks of support, complete and sustained recovery from myocarditis was observed.